Some comments on the functions of bilingual dictionaries (Eurasian Journal of Humanities and Social Sciences, 2022)
Traditionally, a bilingual dictionary was called a translation dictionary and indeed, the translation of texts was the main goal of creating of such dictionaries. Bilingual dictionaries arose in connection with the development of political, economic, and cultural ties between peoples. Bilingual dictionaries provide the users with information about the vocabulary and grammar of another language, as well as concepts about a different culture, a different vision of the world. This article provides an overview on the main functions of bilingual dictionaries